2008
DOI: 10.1242/jeb.019836
|View full text |Cite
|
Sign up to set email alerts
|

The physiology of the midgut ofLutzomyia longipalpis(Lutz and Neiva 1912): pH in different physiological conditions and mechanisms involved in its control

Abstract: SUMMARYNutrient digestion and absorption after blood feeding are important events for Lutzomyia longipalpis, which uses these nutrients to produce eggs. In this context, the pH inside the digestive tract is an important physiological feature as it can markedly influence the digestive process as well as interfere with Leishmania development in infected phlebotomines. It was described previously that unfed females have an acidic midgut (pH 6). In this study, the pH inside the midgut of blood-fed females was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
62
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 39 publications
4
62
0
6
Order By: Relevance
“…We have previously reported that the pH of the diverticulum in L. longipalpis females assumes the value of the ingested food, reflecting an unbuffered condition (Santos et al, 2008). However, the pH in the abdominal midgut is rigorously adjusted according to the physiological state.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously reported that the pH of the diverticulum in L. longipalpis females assumes the value of the ingested food, reflecting an unbuffered condition (Santos et al, 2008). However, the pH in the abdominal midgut is rigorously adjusted according to the physiological state.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pH in the abdominal midgut is rigorously adjusted according to the physiological state. In unfed or sugar-fed insects, the midgut pH is actively maintained at ~6, even when it is challenged by ingestion of strong buffered solutions such as 0.16moll -l HEPES pH7.5 or 0.16moll -l MES pH5.0 (Santos et al, 2008). The intestinal enzyme -glucosidase, which digests carbohydrates that are typically found in the sugar diet, requires an acidic pH (Gontijo et al, 1998;Jacobson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations